Guías prácticas y herramienta para apoyar el desarrollo de sitios web accesibles - Londoño-Rojas, Luis-Felipe; Tabares-Morales, Valentina; Bez, Marta-Rosecler; Duque-Méndez, Néstor-Darío (Revista Científica, 2021)
The massive development of websites and management of the information on the web has generated an exclusion problem for many people, especially those with some type of disability. This is generally due to the fact that websites are not accessible from the source code, as developers are not aware of the norms and standards for their development or their understanding is not facilitated during their application. This hinders the correct functioning of assistive tools for people with disabilities to navigate these websites. This work presents a series of practical guidelines for accessible coding to offer an alternative to developers, aimed to facilitate the implementation of accessibility features by using practical and interactive examples. To guarantee availability and validate the proposed guidelines, the GPCA tool was developed, which presents the proposed guidelines and support elements for developers.